HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN SELF EFFICACY PADA REMAJA DI SMU NEGERI 9 YOGYAKARTA - Niken Widanarti; Aisah Indati (Faculty of Psychology, Universitas Gadjah Mada, 2002)
The purpose of this research is to know the correlation between family social support and self-efficacy of adolescent. Its hypothesis, there is any positive correlation between family social support and self-efficacy of adolescent. More higher to get family social support, more higher to get self efficacy. While more lower to get family social support, more lower to get self efficacy. The subject of this research, the first and the second class of senior high school students in SMU Negeri 9 Yogyakarta with the average age between 14 to 18 years old and the total number are 143 persons. The validity used is content validity while reliability test uses coefficient technique of Alpha reliability from Cronbach. Data analysis uses correlation technique of Product Moment from Pearson. Normality test result with Kolmogorov Smirnov of Fit Test (K-SZ) points out that the variable of self efficacy has coefficient K-SZ=0,535 with p>0,05 while the variable of family social support has coefficient K-SZ=0,763 with p>0,05 howing both variables having normal distribution. The result of linierity test between both variables has value F=47,708 with p